First‐Principles Investigation of β‐FeOOH for Hydrogen Evolution: Identifying Reactive Sites and Boosting Surface Reactions. Issue 31 (8th May 2020) - Huang, Zhenxiong; Guan, Xiangjiu; Li, Mingtao; Guo, Liejin
Abstract: Akaganeite (β‐FeOOH) is a widely investigated candidate for photo(electro)catalysis, such as water splitting. Nevertheless, insights into understanding the surface reaction between water and β‐FeOOH, in particular, the hydrogen evolution reaction (HER), are still insufficient. Herein, a set of first‐principles calculations on pristine β‐FeOOH and halogen‐substituted β‐FeOOH are applied to evaluate the HER performance through the computational hydrogen electrode model. The results show that the HER on β‐FeOOH tends to occur at Fe sites on the (010) surface, and palladium and nickel are found to serve as excellent co‐catalysts to boost the HER process, due to the remarkably reduced free energy change of hydrogen adsorption upon loading on the surface of β‐FeOOH, demonstrating great potential for efficient water splitting. Abstract : Faster evolution : The hydrogen evolution reaction (HER) on β‐FeOOH surfaces is investigated by DFT calculations. Two possible reaction pathways on (001) and (010) surface are discussed. The interaction between hydrogen and surface reaction sites is influenced by the surrounding chemical environment. The HER performance can also be significantly boosted by metal co‐catalyst loading.